Bioassay of new chemistry insecticides against pod borer, Helicoverpa armigera on chickpea - Jat, B L; Yadav, S S; Lal, Roshan (Indian Journal of Plant Protection, 2020)
Toxicity of different insecticides was evaluated against 2nd and 3rd instar larvae of Helicoverpa armigera under laboratory conditions by leaf dipping method. The insecticides viz., thiodicarb 75WP, novaluron 10EC, spinetroam 11.7EC, indoxacarb 15.8EC, quinalphos 25EC, rynaxypyr 18.5SC, emamectin benzoate 5SG and cypermethrin 25EC were tested. Spinetoram was found most effective in managing the 2nd instar larvae of H. armigera and it was followed by novaluron 10EC and indoxacarb 15.8EC as compared to cypermethrin 25EC. Emamectin benzoate 5SG @ 1 x 10-7 to 1 x 10-9 per cent concentrations recorded 100% mortality against 2nd instar larvae and LC50 values for 3rd instar larvae was 0.00000000045%. Insecticides novaluron 10EC, spinetoram 11.7EC andÂ cypermethrin 25EC did not show promising and consistent results against 3rd instar larvae of H. armigera at 24 hrs. The LT50 of novaluron 10EC at 0.00005% concentration was 19.861 hrs and it was 28.144 hrs at 0.000001% against 2nd instar larvae of H. armigera.